SANKSI ADAT PELAKU PEMERKOSAAN ANAK DI BAWAH UMUR DI SUKU PASEMAH MENURUT HUKUM ADAT PASEMAH(Menurut perspektif UU Perlindungan anak pasal 81 dan 82, Studi Kasus di Kecamatan Kelam Tengah, Bengkulu) - Shinta Dila Pinastiti; I Nengah Suastika; I Wayan Lasmawan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2023)
This thesis is entitled Traditional Sanctions for Underage Rape Perpetrators in Pasemah Traditional Village with Pasemah Customary Law (perspective of Child Protection Law Articles 81 and 82). The background of this research is the imbalance in giving sanctions to the perpetrators of rape in the Pasemah Traditional Village. The purpose of this study was to find out the system of imposing customary sanctions for perpetrators of rape in the Adat Pasemah Village, to find out the views of the community regarding the customary sanctions given to perpetrators of rape in the Traditional Village of Pasemah, and to find out the suitability of customary sanctions for perpetrators of rape with the sanctions contained in Articles 81 and 82 of the Child Protection Act. This research is a descriptive qualitative research with data collection methods in the form of interviews, observation, and documentation studies. And this research was conducted in Pasemah Village, Kelam Tengah District, Kaur Regency, Bengkulu. Based on the research that has been done, the researchers found a discrepancy between the traditional sanctions given to the perpetrators of rape and the sanctions contained in the Child Protection Act articles 81 and 82. Some people think that the customary sanctions given to the perpetrators of rape are not in accordance with the sanctions in the legal system national law.